Wyniki badania kluczowych czynników sukcesu przedsięwzięć informatycznych - Dyczkowski, Mirosław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The paper presents results of a study, which aimed at acquiring data on key success and failure factors in IT-projects. The survey, carried out by the author in 2005, comprised 190 IT-projects implemented in various businesses and institutions. In the initial part of the article basic features of the analysed projects and companies are characterised. A quantitative analysis of planned and actual schedules and budgets of the projects, as well as qualitative evaluation of compliance of their scope with customer's requirements are presented subsequently. Eventually, the conclusions are drawn and further directions of research identified. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 125-139